Afterword: a view from enaction. (January 2019) - Stewart, John
Abstract: Enaction is the process whereby a living organism brings about its own Umwelt or lived-world of experience. The prototype example is the "the world of the tick" as described by von Uexküll. This is a nice case of simplexity – achieving an impressive result by apparently simple means. Thus, the modest tick, blind and deaf and only capable of crawling slowly, achieves the task of catching a mammal – thousands of times bigger and faster – and getting to suck its blood. The means in question involve chaining three perception-action cycles: sensing butyric acid (emitted by the sweat glands of mammals) which causes the tick to drop; crawling on a rough surface until finding a smooth surface (in context, the bare skin of the mammal); and sucking a liquid at 37 °C underneath the surface (in context, the blood of the mammal). The notion of simplexity is attractive, especially to those biologists who still retain « a feeling for the organism ». However, the concept of simplexity has its limitations; it does not explain anything, it is essentially an appreciation which comes after the event. Indeed one might even go so far as to say that simplexity is not so much a solution, but rather a problem which itself requires explanation. After commenting on each of the texts in this volume, I found no substantial indications that "simplexity" does actually explain anything. My conclusion is that "simplexity", far from being an explanation, is rather an alert flag for situations which are certainly interesting, but which are in need of further study and explanation. In this sense, "simplexity" is indeed a useful heuristic – although perhaps not in quite the way that was originally intended.